2009
DOI: 10.4038/gmj.v11i1.1111
|View full text |Cite
|
Sign up to set email alerts
|

The position, dimensions and morphological variations of mental foamen in mandibles

Abstract: Introduction: Mental foramen (MF) is a small foramen situated in antero lateral aspect of the body of the mandible. It transmits mental nerve, artery and vein. Studying the position and its morphological variations of MF helps to localise the mental nerve which is a branch of the inferior alveolar nerve. It will help to prevent complications during invasive procedures at the mental region. The most common position of the MF is in-line with the longitudinal axis of the 2 nd pre-molar tooth followed by a locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 5 publications
5
28
2
1
Order By: Relevance
“…[36] In the study conducted by Virendra B et al [6] the incidence of AMF was found 6.6%. AMF was found in 5.81% in the study conducted by Zhang L et al [35] As can be seen from the above Table-I, it could be ascertained that the incidence of occurrence of AMF as reported by various workers was found ranging from 2.67% to 8.33%, with the finding in the present study (8%) very close to the findings of Prabodha et al [13] Sl. No.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…[36] In the study conducted by Virendra B et al [6] the incidence of AMF was found 6.6%. AMF was found in 5.81% in the study conducted by Zhang L et al [35] As can be seen from the above Table-I, it could be ascertained that the incidence of occurrence of AMF as reported by various workers was found ranging from 2.67% to 8.33%, with the finding in the present study (8%) very close to the findings of Prabodha et al [13] Sl. No.…”
Section: Resultssupporting
confidence: 87%
“…[7] Some samples of the mandibles showing the location, size, shape and position of MF and AMF studied in the present study are shown below As can be seen from Fig. 5, it could be observed that the mean diameter size of oval shape MF of our study was found almost similar to the findings of Prabodha et al [13] and Priya PR et al [29] and very close to that of Rahul Rai et al [30] Udhaya K et al [1] , Mesbahul H et al [17] , Sumit G et al [31] Alma Voljevica et al [20] and Gerhenson A et al [32] whereas in the case of round shape it was found closer to the findings of Udhaya K et al [1] Sumit G et al [31] and Oliveira Junior et al [19] As regards the shapes of MF reported by different workers, the above Bar Diagram showed that the occurrence of both oval and round shape MF in our study was found almost in conformity with the findings of Udhaya K et al [1] and Alma Voljevica et al [20] Table-I The incidence of AMF varies in the literature. [6] Singh R and Srivastav AK observed AMF in 13% mandibles.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The mental foramen was symmetrically positioned in majority of cases and this was in agreement with results in other ethnic groups Turkish 90.4%, North Jordanian 77%. According to Philips et al 17 , the size of the foramen on panoramic radiographs appeared slightly larger than those on peri-apical radiographs. However, the horizontal position of the mental foramen on panoramic radiographs was similar with the position reported on peri-apical radiographs.…”
mentioning
confidence: 93%